PENGEMBANGAN PROSES THERMOKIMIA UNTUK PENINGKATAN KONVERSI ASAM LEMAK MELALUI INTERFACIAL ACTIVATION LIPASE BUAH SEGAR KELAPA SAWIT DENGAN TUNING UP MENGGUNAKAN GELOMBANG MIKRO - Wikanta, Deddy Kurniawan; Y, Mohamad Endy; Erlangga, Erlangga; A, Hermawan Dwi (Universitas Diponegoro, 2012)
Nowadays, Indonesia fulfill the demand of fatty acid by importing it, through Indonesia is one of major producer of Crude Palm Oil (CPO), one of vegetable oil beside Palm Kernel Oil (PKO) and Coconut Oil (CNO) that can be used as the raw material for the production of fatty acid. In order to increase the added value of palm oil and to fulfill the country demand of fatty acid, it is necessary, finding a new fatty acid production process which is more efficient and more economial. Because palm oil has a lipase enzyme that can hydrolyze the triglyceride of palm oil, it is urge to study the technology of fatty acid production by utilize the lipase of palm oil. The thermal protonation of microwave toward the fatty acid chain in enzyme is the important matter, because enzyme will memorize the ionization condition from aquatic solution before the dehydration process (enzyme’s pH memory). Because of that, “the tuning” towards pH will fasten the hydrolysis rate. The parameters of the research were reaction temperature, pH, power, ratio of water-fruit, mechanical treatment and the milling of the palm oil as time function. Keywords : fatty acid, lipase enzyme, interfacial antivation, microwave